The Effects of Drying and Wetting on the Soil Chemical Properties of Acid Sulphate Soils of Kalimantan - M. NOOR; A. MAAS; T. NOTOHADIKUSUMO (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2008)
This research aimed to study the effects of land reclamation (drying, wetting, flushing, and leaching) on the change of soil chemical properties of acid sulphate soils from Kalimantan. Randomized Complete Design (RCD) by two factors treatments with two replications is used in this research. Factor I was soil reactiveness that is define as (a) low reactive= R1; (b)moderate reactive =R2; (c) strong reactive= R3, and (d) very strong reactive= R4 respectively. Factor II was drying, wetting, and diluting that is define as (1) drying continuously after wetting = W1, (2) wetting continuously = W2; (3) drying after weeting and diluting =W3; and (4) wetting and diluting. The result of experiments show that continuous drying after wetting (W1) and drying after wetting and diluting (W3) or continuous weeting (W2) gave soils pH lower than the weeting and diluting (W4).Dried on the strong reactive soils (R4) not decrease soil pH significantly. The continouos drying after wetting (W1) can increase EC (electrical conductivity) higher than the continous wetting (W2) and wetting that followed diluting (W4) or drying after wetting and diluting (W3). The continouos wetting (W2) and the continouos drying after wetting (W1) has given the total soluble acidity of 63,30 dan 61,71 cmolc kg-1 respectively, higher than drying after wetting and diluting (W3) and wetting thatfollowed diluting (W4) that given total soluble acidity of 54,03 and 51,95 cmolc kg-1 respectively. The effects of drying, wetting, flushing, and leaching on the total soluble acidity, Soluble Al and soluble H, especially on the strong reactive soils are very significant. All of the exchangeble bases (Ca, Mg, K, Na) on the continouos drying after wetting (W1) are lower than the continous wetting (W2) and wetting that followed diluting (W4)or drying after wetting and diluting (W3) respectively. The continouos drying after wetting (W1), the continous wetting (W2) and wetting that follow diluting (W4) or drying after wetting and diluting (W3) decrease exchangable Mg, especially on strong reactive soils (R4), but contradictive to low reactive soils (R1). The continouos drying after wetting (W1) increase exchangable Na, especially on low reactive soils (R1), but the wetting that followed diluting (W3, W4) decreases exchangable Na.